2014
DOI: 10.2478/botcro-2013-0021
|View full text |Cite
|
Sign up to set email alerts
|

Succession rates and patterns twelve years after land use abandonment in the estuary of the river aliakmon, n. greece

Abstract: -Vegetation succession is a key element for research studying biodiversity losses, effects of climatic change on ecosystems, invasive species and restoration of ecosystems in which human activities have shifted their natural or semi-natural vegetation. Surrogate variables like Pignatti's bioindicator values or dissimilarity indices can provide further insights regarding succession trajectories aggregating the combined effects of changes in the cover/abundance of taxa. The land-use abandonment in an area in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…During the last examined period , in most of the deltaic areas studied, the surface cover of agricultural land remained stable, decreased or, at least, did not increase with the same rates as those seen in the period from 1945 to 1975. The observed increased cover of natural LULC classes can be attributed to restoration projects that allowed the regrowth of natural ecosystems in deltaic areas [109] or, in some cases, due to extended salinization of areas that had been earlier delivered to agricultural exploitation following drainage projects. These fields were abandoned, and secondary vegetation succession drove LULC changes towards natural vegetation classes.…”
Section: Discussionmentioning
confidence: 99%
“…During the last examined period , in most of the deltaic areas studied, the surface cover of agricultural land remained stable, decreased or, at least, did not increase with the same rates as those seen in the period from 1945 to 1975. The observed increased cover of natural LULC classes can be attributed to restoration projects that allowed the regrowth of natural ecosystems in deltaic areas [109] or, in some cases, due to extended salinization of areas that had been earlier delivered to agricultural exploitation following drainage projects. These fields were abandoned, and secondary vegetation succession drove LULC changes towards natural vegetation classes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that above‐ground vegetation biomass may increase for ca 80 years before reaching an equilibrium (Bose, Schelhaas, Mazerolle, & Bongers, ). Thus, we consider that vegetation succession is an on‐going process in our study area, leading to an expected species richness increase in the future (Grashof‐Bokdam & Geertsema, ; Harmer, Peterken, Kerr, & Poulton, ; Rivera, Zimmerman, & Aide, ; Xystrakis et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The habitat types and the related vegetation of the Natura 2000 site "Stena Kalamakiou" (GR 1440004) in the plain of Thessalian Pinios river were briefly described by Theodoropoulos et al (2006), whilst essential knowledge on land-use/vegetation cover relationships was given for the riparian areas of Nestos river (Zaimes et al 2011a). Few studies have also focused on the vegetation of some river deltas (Babalonas 1979, Georgiadis et al 1997, Economidou 1998, Karagiannakidou et al 2000, Korakis & Gerasimidis 2006, Xystrakis et al 2014.…”
Section: Introductionmentioning
confidence: 99%